Mast cell degranulation distinctly activates trigemino-cervical and lumbosacral pain pathways and elicits widespread tactile pain hypersensitivity - Levy, Dan (2011)
Mast cells (MCs) are tissue resident immune cells that participate in a variety of allergic and other inflammatory conditions. In most tissues, MCs are found in close proximity to nerve endings of primary afferent neurons that signal pain (i.e. nociceptors). Activation of MCs causes the release of a plethora of mediators that can activate these nociceptors and promote pain. Although MCs are ubiquitous, conditions associated with systemic MC activation give rise primarily to two major types of pain, headache and visceral pain. In this study we therefore examined the extent to which systemic MC degranulation induced by intraperitoneal administration of the MC secretagogue compound 48/80 activates pain pathways that originate in different parts of the body and studied whether this action can lead to development of behavioral pain hypersensitivity. Using c-fos expression as a marker of central nervous system neural activation, we found that intraperitoneal administration of 48/80 leads to the activation of dorsal horn neurons at two specific levels of the spinal cord; one responsible for processing cranial pain, at the medullary/C2 level, and one that processes pelvic visceral pain, at the caudal lumbar/rostral sacral level (L6-S2). Using behavioral sensory testing, we found that this nociceptive activation is associated with development of widespread tactile pain hypersensitivity within and outside the body regions corresponding to the activated spinal levels. Our data provide a neural basis for understanding the primacy of headache and visceral pain in conditions that involve systemic MC degranulation. Our data further suggest that MC activation may lead to widespread tactile pain hypersensitivity.